The Literary Study on Ashwagandha (Withania Somnifera) - A Review Article - Choudhary, Tarun; Mishra, Shiromani (International Research Journal of Ayurveda & Yoga, 2021)
As a Rasayana, Ashwagandha is a highly appreciated plant in the Indian Ayurvedic medical system. It’s used for a variety of ailments, but most notably as a nervine tonic. Many scientific investigations on its adaptogenic and anti-stress properties have been conducted in light of these findings. It has been demonstrated to aid youngsters with memory impairments as well as senior persons with memory loss. It’s also been demonstrated to help those with neurological diseases such as Parkinson’s, Huntington’s, and Alzheimer’s disease. The drug possesses anti-inflammatory, anti-arthritic, cardio protective, anti stress, tranquilizer-like sedative characteristics and has been shown to be an effective treatment for malignant development in numerous organs.